Marketing management in action - Buell, Victor P (McGrawHill, 1966)
The book outlines the scope and functions of the marketing manager's job, his place in the corporate, organization, his authority and his relationships. It illustrates how the management tools of organization, planning, direction and control are applied to the marketing sutuation. The book also describes the four avenues of growth available to any company and discusses the advantages and disadvantages of each.